Pharmacokinetic-pharmacodynamic modeling of electroencephalographic effects of midazolam in eight Chinese men - Lu Jian-feng; Chen Gang; Xiang Ben-ren; An Deng-kui (Acta Pharmacologica Sinica, 2016)
The effects of midazolam (Mid) on the electroencephalogram (EEG) were related to Mid concentrations in serum in 8 Chinese healthy male volunteers for the assessment of concentration-effect relationship. The total number of waves per second within the frequency range of 12-30 Hz (TNW12-30) in the central-occipital (C1-O1) lead EEG obtained by aperiodic analysis was used as EEG effect of the drug. The PK-PD parameters were calculated by PK-PD software using the sigmoid Emax model. They were: T1(2)keo = 1.3 +/- 0.9 min-1, EC50 = 254 +/- 54 micrograms.L-1, N = 2.9 +/- 0.6. E0 and Emax were calculated from the observed values, being 3.4 +/- 1.3 and 11.4 +/- 2.2 TNW12-30, respectively. Our results showed that the concentration-EEG effect relationship of Mid could be characterized in individual Chinese man using TNW12-30 as a measure of pharmacological response.